Expression and functional role of neuronal alpha7 nicotinic receptor in human NK cells - Zanetti, Samanta Romina (2016)
An entire neuronal cholinergic system has been detected in immune cells, but the functional relevance of this extra- neuronal cholinergic system remains ill-de ned. The alpha7 nicotinic receptor is one of the most abundant in the central nervous system and it is emerging as an important drug target for neurological disorders. Alpha7 is also present in immune cells, and it is an important player of the cholinergic anti-in ammatory pathway which links the nervous with the immune systems.